Analysis of the form characteristics of traditional dwellings in the Tongchuan area of Shaanxi Province, China - Penghui Zhao; Liyue Wu; Yanjun Li (Journal of Asian Architecture and Building Engineering)
Tongchuan, Shaanxi Province, China, is known for its diverse culture and history. Tongchuan residents have created a unique creative and aesthetic sensibility. Geographic location, environment, and varied humanistic activities have shaped regional culture. A distinctive architectural cultural history has helped build architectural culture in Weibei, Guanzhong, China. Tongchuan’s culture shaped its architecture. Mapping records, image and data gathering, and field investigations were used to study traditional dwellings in the area. Tongchuan’s traditional dwellings were analyzed and illustrated simultaneously. Courtyard and kiln dwellings were used to map and study traditional dwelling architecture. A database of Tongchuan’s traditional dwellings is essential for cultural preservation. This method replicates and spreads traditional residential structures and provides data for architectural culture studies. The research findings were intended to serve as guidance for future Tongchuan’s traditional dwelling studies. While developing new rural areas in China, traditional villages must be preserved.